Enhanced Condensation on Soft Materials through Bulk Lubricant Infusion (Adv. Funct. Mater. 17/2022). (25th April 2022) - Sharma, Chander Shekhar; Milionis, Athanasios; Naga, Abhinav; Lam, Cheuk Wing Edmond; Rodriguez, Gabriel; Del Ponte, Marco Francesco; Negri, Valentina; Raoul, Hopf; D'Acunzi, Maria; Butt, Hans‐Jürgen; Vollmer, Doris; Poulikakos, Dimos
Abstract : Bulk Lubricant Infusion In article number 2109633, Dimos Poulikakos and co‐workers show that bulk lubricant infusion in soft materials can significantly increase condensate droplet shedding through a large reduction in viscoelastic dissipation, while simultaneously promoting high droplet nucleation density. This behavior markedly enhances water condensation and promotes the suitability of such materials for passive water harvesting.